Simulation and experimental study of enzyme and reactant mixing in capillary electrophoresis based on-line methods - Pelcová, Marta; Řemínek, Roman; Sandbaumhüter, Friederike A; Mosher, Richard A; Glatz, Zdeněk; Thormann, Wolfgang (Journal of chromatography. A, 2016)
The establishment of an efficient reaction mixture represents a crucial part of capillary electrophoresis based on-line enzymatic assays. For ketamine N-demethylation to norketamine mediated by the cytochrome P450 3A4 enzyme, mixing of enzyme and reactants in the incubation buffer at physiological pH was studied by computer simulation. A dynamic electrophoretic simulator that encompasses Taylor-Aris diffusivity which accounts for dispersion due to the parabolic flow profile associated with pressure driven flow was utilized. The simulator in the diffusion mode was used to predict transverse diffusional reactant mixing occurring during hydrodynamic plug injection of configurations featuring four and seven plugs. The same simulator in the electrophoretic mode was applied to study electrophoretic reactant mixing caused by voltage application in absence of buffer flow. Resulting conclusions were experimentally verified with enantioselective analysis of norketamine in a background electrolyte at low pH. Furthermore, simulations visualize buffer changes that occur upon power application between incubation buffer and background electrolyte and have an influence on the reaction mixture.
Keywords: hydrodynamika; Cytochrome P-450 CYP3A; ketamin; enzymatické testy; difuze; Capillary electrophoresis; elektroforéza kapilární; Simulation; Buffers; Taylor-Aris dispersion; Enzyme Assays; Diffusion; pufry; počítačová simulace; Enzyme reaction; Computer Simulation; cytochrom P-450 CYP3A; Ketamine; Electrophoretically mediated microanalysis; Electrophoresis, Capillary; Hydrodynamics